Peningkatan Kemampuan Berbahasa Inggris Dan Kecintaan Terhadap Budaya Lokal Oleh Generasi Muda SMK Bintang Persada di Desa Padangsambian Kaja - I Gusti Ayu Agung Dian Susanthi; I Made Mardika; Made Sani Damayanthi Muliawan; Opirman Waruwu; Sri Indriani Duha; Ni Luh Pegy Wilantari; Niken Ardila Rehiraky (Postgraduated Community Service Journal, 2025)
The introduction of local culture and products to the international realm is very important to note. One thing that can be done as an effort to support is to improve English language skills. In line with this, of course, Bali as a world tourist destination has an impact on the behavior of its people. For the younger generation in Bali, having good English skills makes it easier for them to get jobs and can increase competitiveness for the welfare of their lives. This causes the attention of the Balinese people to prioritize the mastery and use of foreign languages. Mastering a foreign language, especially English, is also thought to increase prestige and open great opportunities to win global competition.